In vitro systems to study inborn errors of immunity using human induced pluripotent stem cells - Nikolouli, Eirini; Reichstein, Janne; Hansen, Gesine; Lachmann, Nico (Frontiers in Immunology, 2022)
In the last two decades, the exponential progress in the field of genetics could reveal the genetic impact on the onset and progression of several diseases affecting the immune system. This knowledge has led to the discovery of more than 400 monogenic germline mutations, also known as “inborn errors of immunity (IEI)”. Given the rarity of various IEI and the clinical diversity as well as the limited available patients’ material, the continuous development of novel cell-based in vitro models to elucidate the cellular and molecular mechanisms involved in the pathogenesis of these diseases is imperative. Focusing on stem cell technologies, this review aims to provide an overview of the current available in vitro models used to study IEI and which could lay the foundation for new therapeutic approaches. We elaborate in particular on the use of induced pluripotent stem cell-based systems and their broad application in studying IEI by establishing also novel infection culture models. The review will critically discuss the current limitations or gaps in the field of stem cell technology as well as the future perspectives from the use of these cell culture systems.